Calling the Greek Referendum on the nose with Google Trends - Nikos Askitas (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2015)
In a bold and risky political move the Greek prime minister Alexis Tsipras called for a referendum on June 27 2015 quitting ongoing negotiations with Greece's creditors in Brussels. The referendum framed as a yes or no question asked the Greek voters to decide whether or not they approve or reject the latest take-it-or-leave-it proposal for "program con- tinuation" by Greece's creditors. What followed was a chaotic week leading to the referendum with intense campaigning by the two camps. Due to tense debates and increasing polarisation it became increasingly impossible to rely on traditional polling. Even the first exit polls (performed by phone on Sunday evening) could only see a marginal lead for one or the other vote at different times. Quite possibly people were jumping party lines and were unwilling to reveal their preferences. Using Google Trends I could tap into voters' true and unbiased revealed preferences and nowcast hourly what the ratio of the No vote to the Yes vote is and called an over 60% No vote well ahead of the closing of the voting urns. In this paper I document this nowcasting exercise.
Keywords: 330; nowcasting; Greek Referendum; greferendum; exit polls; complexity; behaviour; data science; computational social science; complex systems